An Earth-sized exoplanet with a Mercury-like composition. (May 2018) - Santerne, A.; Brugger, B.; Armstrong, D.; Adibekyan, V.; Lillo-Box, J.; Gosselin, H.; Aguichine, A.; Almenara, J.-M.; Barrado, D.; Barros, S.; Bayliss, D.; Boisse, I.; et al.
Abstract Earth, Venus, Mars and some extrasolar terrestrial planets1 have a mass and radius that is consistent with a mass fraction of about 30% metallic core and 70% silicate mantle2 . At the inner frontier of the Solar System, Mercury has a completely different composition, with a mass fraction of about 70% metallic core and 30% silicate mantle3 . Several formation or evolution scenarios are proposed to explain this metal-rich composition, such as a giant impact4, mantle evaporation5 or the depletion of silicate at the inner edge of the protoplanetary disk6 . These scenarios are still strongly debated. Here, we report the discovery of a multiple transiting planetary system (K2-229) in which the inner planet has a radius of 1.165 ± 0.066 Earth radii and a mass of 2.59 ± 0.43 Earth masses. This Earth-sized planet thus has a core-mass fraction that is compatible with that of Mercury, although it was expected to be similar to that of Earth based on host-star chemistry7 . This larger Mercury analogue either formed with a very peculiar composition or has evolved, for example, by losing part of its mantle. Further characterization of Mercury-like exoplanets such as K2-229 b will help to put the detailed in situ observations of Mercury (with MESSENGER and BepiColombo8 ) into the global context of the formation and evolution of solar and extrasolar terrestrial planets. The abundance of metals in Mercury's interior is unique among the rocky planets of the Solar System. The characterization of the 'super-Mercury' exoplanet presented in this paper will improve our understanding of how Mercury-like planets can form and evolve.